Multiplication of Binomial by Binomial

Multiplication of Binomial by Binomial, we use a FOIL method.

F = First terms

O = Outer terms

I = Inner terms

L = Last terms


Example:
1)


2) (2x -1)(5x +6)

Solution :
= (2x
. 5x)+ (2x . 6) + (-1 . 5)+ (-1 . 6)
= 10x
2+ 12x - 5x -6 (add like terms)
= 10x
2 + 7x - 6

3) (8x - 3)( 9x -2)

Solution :
= (8x
. 9x)+ (8x . -2)+ (-3 . 9x) + (-3 . -2)
= 72x
2 - 16x - 27x + 6
=72x
2 - 43x + 6

4) (y + 2) ( y - 2)

Solution :
= (y
. y)+ (7 . -2)+ (2 . y)+ (2 . -2)
= y
2 + 2y - 2y - 4
= y
2 + 0 - 4
= y
2 - 4

5) (x
2 + 5)(x 2 + 10)

Solution :
= (x
2 . x 2 )+ (x 2 . 10)+ (5 . x 2 )+ (5 . 10)
= x
2 + 2 + 10x2 + 5x2 + 50
= x
4 + 15x 2 + 50

6) (2x
2 + 8)(x 2 - 7)

Solution :
= (2x
2 . x 2 )+ (2x 2 . (-7)+ (8 . x 2 )+ (8 . (-7)
= 2x
2 + 2 - 14x2 + 8x2 -56
= 2x
4 - 6x 2 - 56
____________________________________________________________________
Practice

1) (4x + 2) (2x - 4)
2) (x + 2) (x - 2)
3) (2a - 6) (a - 4)
4) (5b + 2) (3a + 4)
5) (-2a + 2) (3a + 9)

Multiplication of algebraic expressions

Multiplication of Monomial by Binomial
Multiplication of Binomial by Binomial
Multiplication of Polynomial by Monomial
Multiplication of Polynomial by Binomial


Algebraic Expressions page

Home Page